Aerobic treatment of liquid wastes from the fruit processing industry - Kitti Kumpeera; Nguyen Cong Thanh; Samorn Muttamara; Yang, Ping Yi; The Government of Netherlands (Bangkok : Asian Institute of Technology, 1976)
The physical, chemical and biological properties of wastewater from the pineapple cannery waste was assessed. The aerobic biological treatment process as batch activated sludge, activated sludge with the constant s ludge recycle and aerated lagoon were studied. Both pine apple cannery waste and diluted-pineapple juice as a synthetic waste were used for study. For batch-activated sludge over 90% COD removal was achieved within 1 hour aeration time. Continuous activated sludge process can provide greater than 95% COD removal with the maximum organic loading of 12.0 kg COD/kg MLSS-day. The design parameters were followed by GAUDY's APPROACH and ECKENFELDER's APPROACH. Aerated lagoon can provide a greater than 90% COD removal with the detention time 2-3 days, but the solids still remain in the effluent. Aerated lagoon followed by polishing pond can provide more than 95% with 6 days detention time and solids in the effluent are minimized.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1976
Keywords: Water -- Purification; Fruit processing -- Waste disposal